Dynamical phase transition in slowed exclusion processes - Franco, Tertuliano (2014)
In this work, we present symmetric simple exclusion processes with a finite number of bonds whose dynamics is slowed down in order to difficult the passage of particles at those bonds. We study the influence of the rate of passage of mass at those bonds in the macroscopic hydrodynamic equation. As a consequence, we exhibit a dynamical phase transition that goes from smooth profiles to the development of discontinuities.